2013
DOI: 10.4103/2231-4040.111526
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of diltiazem hydrochloride controlled-release pellets by fluid bed coating process

Abstract: The aim of the present study was to develop controlled-release pellets of diltiazem HCl with ethyl cellulose and hydroxylpropyl methylcellulose phthalate as the release rate retarding polymers by fluid bed coating technique. The prepared pellets were evaluated for drug content, particle size, subjected to Scanning Electron Microscopy (SEM) and Differential Scanning Calori metry (DSC), and evaluated for in vitro release. Stability studies were carried out on the optimized formulations for a period of 3 months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…MCC has better spheronizing capacity than lactose. [ 23 24 ] But, the extrudate prepared with MCC PH 102 showed cracks with a granular surface which did not observed in case of MCC PH 101. Hence, MCC PH 101 was selected as spheronizing aid for further study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MCC has better spheronizing capacity than lactose. [ 23 24 ] But, the extrudate prepared with MCC PH 102 showed cracks with a granular surface which did not observed in case of MCC PH 101. Hence, MCC PH 101 was selected as spheronizing aid for further study.…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed that there was no major interaction or complexation between the drug and the wax throughout the process of pelletization. [ 24 ]…”
Section: Resultsmentioning
confidence: 99%
“…The countless number of existing and novel drugs, however, has led to continuous efforts to establish new formulas, technologies, and devices to regulate their release profiles [ 10 ]. The majority of studies have been focused on enhancing drug bioavailability and reducing dosing frequencies [ 11 , 12 ]. This can be achieved by several pharmaceutical approaches, including, for example, coating systems [ 13 ], osmotic pressure systems [ 14 ], and matrices systems [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fluidization aspect of this process enables an in-device drying step to reduce the residual solvent level, thereby circumventing a transfer to a post-drying device, and thus further minimizing potential stability issues. The versatility of the device also allows for the subsequent application of an additional coating layer, either to serve as a drug release rate controlling membrane or as a protection barrier against surface crystallization [ 12 ]. In addition to process-related advantages, bead coating also offers interesting opportunities concerning clinical aspects.…”
Section: Introductionmentioning
confidence: 99%